Answer:
hweee yvgc g. chuvu uvj u h h j j j j jvi
<span>(x + 6)(4x + 1) </span>
<span>x times 4x = 4x^2 </span>
<span>x times 1 = x </span>
<span>6 times 4x = 24x </span>
<span>6 times 1 = 6 </span>
<span>Now add like terms and you get 4x^2 + 25x + 6 </span>
Y=2x-1
y=-3x+14
First you would substitue one of the y's for the other so
2x-1=-3x+14
no you would solve for x...
add one on both sides
2x=-3x+15
now add 3x to both sides which becomes
5x=15
divide 5 on both sides which gives you x=3
now to solve for y plug into any one of the equations(doesn't matter which one) from before 3 for x and solve
y=2(3)-1
y=6-1
y=5
And that is you answer y=5
Answer:
37.5 or 37 1/2
Step-by-step explanation:
You need to multiply length times width times height and then divide it by two.
The value of the given expression after addition is 199 and this can not written as a mixed number in the simplest form.
According to the question,
We have the following expression:
212+(-13)
Now, we know that the multiplication of one negative and one positive integers is always positive.
So, we have the following expression:
212-13
199
Now, this number is whole number and it can not be written as a mixed number. It could only have been written as a mixed number when the result would have been in a fraction.
Hence, the value of the given expression after addition is 199 and this can not written as a mixed number in the simplest form.
To know more about addition here
brainly.com/question/19867930
#SPJ1